A bias-ed assessment of the use of SNPs in human complex traits - Terwilliger, Joseph D.; Haghighi, Fatemeh; Hiekkalinna, Tero S.; Göring, Harald H.H. (Current Opinion in Genetics & Development, 2002)
Although many biotechnological advancements have been made in the past decade, there has been very limited success in unraveling the genetic component of complex traits. Heavily invested research has been initiated based on etiological models of unrealistic simplicity and conducted under poor experimental designs, on data sets of insufficient size, leading to an overestimation of the effect sizes of genetic variants and the quantity and quality of linkage disequilibrium (LD). Arguments about whether families or unrelated individuals provide more power for gene mapping have been erroneously debated as issues of whether linkage or LD are more detectable sorts of correlation. Although the latter issue may be subject to debate, there is no doubt that family-based analysis is more powerful for detecting linkage and/or LD. If the recent advances in biotechnology are to be exploited effectively, vastly improved study designs will be imperative, as the reasons for the lack of success to date have much more to do with biology than technology, an issue that has become increasingly clear with the findings of the past years. Despite biotechnological advances, we have made very little progress in understanding the genetic components of complex diseases. Temptations to plan future research directions based on the hype surrounding the ‘post-genomic euphoria’ rather than substantive scientific argument must be carefully avoided.